Engineering Applications of Diamond - Mallik, Awadesh (IntechOpen, 2021)
Diamond offers many advantages over other wide-bandgap materials and thus is a very important material in engineering applications. It can be used in high-speed electronics and response systems as well as high-power laser windows, protective coatings, electrochemical sensors, and more. This book examines the properties, advantages, and potential applications of diamonds in engineering and other fields.